Intracerebral hemorrhage after deep brain stimulation surgery guided with microelectrode recording: analysis of 297 procedures - Beatriz Mariana Sousa dos Santos (2021)
Background: Intracerebral hemorrhage (ICH) is a feared complication of deep brain stimulation (DBS). The incidence of ICH and the risk factors for its development after DBS guided with microelectrode recording (MER) were analysed. Methods: We performed a retrospective observational study. 297 DBS procedures were concluded in 277 patients in a single hospital centre between January 2010 and December 2020. All surgeries were guided with MER. We analysed the incidence of symptomatic and asymptomatic ICH and its correlation to age, sex, diagnosis, hypertension and perioperative hypertension, diabetes, dyslipidaemia, antiplatelet drugs, anatomic target, and number of MER trajectories. Results: There were a total of 585 electrodes implanted in 277 patients. 16 ICH were observed, of which 6 were symptomatic and 10 asymptomatic, none of which incurred in permanent neurological deficit. The incidence of ICH per lead-implantation was 2.7%. Male patients or with hypertension are 2.7 and 2.2 times more likely to develop ICH, respectively. However, none of these characteristics has been shown to have a statistically significant association with the occurrence of ICH, as well as age, diagnosis, diabetes, dyslipidaemia, antiplatelet drugs, anatomic target, number of MER trajectories and perioperative hypertension. Conclusions: MER-guided DBS is a safe technique, with low incidence of ICH and no permanent deficits in our study. Hypertension and male sex seem to be risk factors for the development of ICH in this surgery. Nevertheless, no statistically significant factors were found for the occurrence of this complication.